Toward better estimation of HVAC Loads: integrating a detailed human thermal model into building simulation. (September 2017) - Rida, Mohamad; Kelly, Nicolas
Abstract: The transient nature of the occupant heat load is not fully addressed and implemented in a building simulation tool. In this paper, the effect of using dynamic occupant heat loads in building simulation on energy building performance and occupant thermal comfort has been studied. A two-node thermoregulatory model was integrated into ESP-r. The predictions of the integrated two-node model were compared to two commonly used approaches in building simulation: gains modelled as a basic fixed profile and gains modelled using a polynomial function of temperature and relative humidity. The variation in occupant thermal load demonstrated appreciable differences on both cooling and dehumidification loads.